2000
DOI: 10.1097/00003246-200010000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maximizing oxygen delivery on morbidity and mortality in high-risk surgical patients

Abstract: Older patients with existing cardiorespiratory illness undergoing major surgery have a reduced morbidity and mortality when dobutamine is used to maximize oxygen transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
3
20

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(143 citation statements)
references
References 48 publications
4
116
3
20
Order By: Relevance
“…27,[34][35][36] However, other clinical trials have reported favorable outcomes with supranormal oxygen delivery. [37][38][39] An optimal approach may be early goal-directed therapy, which has been shown to reduce mortality for patients with severe sepsis and septic shock. 40 This approach involves adjustments of cardiac preload, afterload, and contractility to balance oxygen delivery with V O 2 .…”
Section: Oxygen Deliverymentioning
confidence: 99%
“…27,[34][35][36] However, other clinical trials have reported favorable outcomes with supranormal oxygen delivery. [37][38][39] An optimal approach may be early goal-directed therapy, which has been shown to reduce mortality for patients with severe sepsis and septic shock. 40 This approach involves adjustments of cardiac preload, afterload, and contractility to balance oxygen delivery with V O 2 .…”
Section: Oxygen Deliverymentioning
confidence: 99%
“…So it seems reasonable to think that manipulating haemodynamics in some patients with pharmacologic agents (fluids and inotropes) to reach predefined goals may expose them to unnecessary risks. In the study reported by Lobo et al (27) 58% of the protocol group patients did not achieve the predefined goals despite the high doses of dobutamine (19±12 mcg kg -1 min -1 vs. 10±5 mcg kg -1 min -1 in achievers) and more fluid (median value 6.5 vs. 4 L). Interestingly, in a recent meta-analysis (11) EGDT with fluids and inotropes in high-risk surgical patients was not associated with an increased risk of cardiac complications, and actually the benefit was most pronounced in patients receiving fluids and inotropes with the use of minimally invasive cardiac output monitors.…”
Section: When or Where To Stop?mentioning
confidence: 89%
“…There have been several prospective randomised peri-operative optimisation studies demonstrating a significantly lower mortality in the intervention group compared to controls [11,13,[23][24][25]. The intervention increased oxygen delivery in a variety of ways.…”
mentioning
confidence: 99%